A molybdenum disulfide / carbon superlattice material, a preparation method and application thereof

CN117766730BActive Publication Date: 2026-10-27NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311830057.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-28
Publication Date
2026-10-27
Estimated Expiration
2043-12-28

AI Technical Summary

Technical Problem

[0006]本发明的目的是针对全固态锂电池正极电子导电性低和电解质与碳接触分解问题,提供一种二硫化钼/碳超晶格材料的制备方法

Benefits of technology

[0036](1)本发明方法具有工艺流程简单,操作容易,可控性好等优点,适用于工业上大规模生产。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117766730B_ABST
    Figure CN117766730B_ABST
Patent Text Reader

Abstract

The application discloses a kind of molybdenum disulfide / carbon superlattice material and its preparation method and application, preparation method includes: by chemical intercalation stripping method, bulk molybdenum disulfide is stripped into single-layer molybdenum disulfide nanosheet with negative charge;Single-layer molybdenum disulfide nanosheet with negative charge and positively charged organic small molecule group are self-assembled into molybdenum disulfide / organic small molecule hybrid by electrostatic adsorption;Molybdenum disulfide / organic small molecule hybrid is dried, annealing, and the molybdenum disulfide / carbon superlattice material is obtained.The preparation method of the application is simple, controllable, and the molybdenum disulfide / carbon superlattice material prepared has high conductivity, stable structure and fast ion diffusion kinetics.When used for full solid-state lithium battery positive electrode, it is not necessary to add additional conductive agent, and the electrochemical performance and stability of the battery can be greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of all-solid-state lithium battery cathodes, specifically relating to a molybdenum disulfide / carbon superlattice material, its preparation method, and its application. Background Technology

[0002] Commercially available lithium-ion batteries typically employ organic electrolytes and porous membranes, which pose safety risks such as leakage, combustion, and explosion. In contrast, all-solid-state lithium batteries, using non-flammable inorganic solid electrolytes, can fundamentally solve the safety problems of traditional lithium-ion batteries. Among various inorganic solid electrolytes, sulfide electrolytes stand out due to their high room-temperature ionic conductivity, low grain boundary resistance, and ease of manufacturing, becoming a hot topic in the research and application of all-solid-state lithium batteries. However, most sulfide electrolytes have a narrow intrinsic electrochemical stability window and are thermodynamically prone to decomposition reactions, which presents a significant challenge to the selection of electrode materials.

[0003] Transition metal sulfides have become promising candidates for high-performance all-solid-state battery cathodes due to their high theoretical specific capacity and good interfacial compatibility with sulfide electrolytes. However, due to their limited electronic conductivity, transition metal sulfides often exhibit slow reaction kinetics. Various conductive carbon additives with excellent electrical properties are commonly used to improve the conductivity of cathode composites, such as vapor-grown carbon fiber (VGCF), acetylene black (AB), and super P.

[0004] Patent document CN113943016A discloses a binary transition metal sulfide, which is a sulfide of transition metals vanadium and chromium, with the chemical formula V. x Cr1-xS2, where the value of x ranges from 0 to x < 1, improves the conductivity of the cathode composite material by adding conductive agents such as carbon black, acetylene black, and carbon nanotubes.

[0005] However, as the contact area between the solid electrolyte and carbon increases, the decomposition kinetics of the sulfide electrolyte are significantly enhanced. These ongoing side reactions accelerate electrolyte degradation, forming a poor interfacial layer between the carbon additive and the electrolyte, leading to increased interfacial impedance and significant capacity decay, posing a serious threat to the cycle stability of all-solid-state lithium batteries. Therefore, pursuing positive electrode active materials with sufficient electronic conductivity and avoiding the use of conductive additives in the cathode are crucial for improving the cycle performance of all-solid-state lithium batteries. Summary of the Invention

[0006] The purpose of this invention is to address the problems of low electronic conductivity in the positive electrode and electrolyte decomposition upon contact with carbon in all-solid-state lithium batteries, by providing a method for preparing molybdenum disulfide / carbon superlattice materials. This method has advantages such as simple process flow, easy operation, good controllability, and the potential for mass production.

[0007] A method for preparing a molybdenum disulfide / carbon superlattice material includes the following steps:

[0008] S1. Bulk molybdenum disulfide is exfoliated into single-layer molybdenum disulfide nanosheets with negative surface charge by chemical intercalation exfoliation method;

[0009] S2. Molybdenum disulfide nanosheets with negative surface charge are electrostatically adsorbed and self-assembled with positively charged organic small molecule groups to form a molybdenum disulfide / organic small molecule hybrid.

[0010] S3. The molybdenum disulfide / organic small molecule hybrid is dried and annealed to obtain molybdenum disulfide / carbon superlattice material.

[0011] This invention first uses a chemical intercalation exfoliation method to exfoliate bulk molybdenum disulfide into single-layer molybdenum disulfide nanosheets with negative surface charges. Then, it forms a molybdenum disulfide / organic small molecule hybrid by electrostatic adsorption self-assembly with positively charged organic small molecule groups, which are alternately stacked with molybdenum disulfide and organic small molecules. Finally, the hybrid material is dried and annealed, and the organic small molecule groups are carbonized at high temperature to obtain molybdenum disulfide / carbon superlattice material.

[0012] In the molybdenum disulfide / carbon superlattice material prepared by this invention, the molybdenum disulfide and carbon layers are stacked alternately, which can adapt to the volume changes during charge-discharge cycles and promote the rapid diffusion of lithium ions. The carbon layers are confined and stabilized between the molybdenum disulfide nanosheets, which can effectively improve the degradation problem of sulfide electrolytes. Thus, the prepared molybdenum disulfide / carbon superlattice material has high conductivity, stable structure and fast ion diffusion kinetics.

[0013] Preferably, in step S1, the step of exfoliating bulk molybdenum disulfide into negatively charged monolayer molybdenum disulfide nanosheets by chemical intercalation exfoliation is as follows:

[0014] S11. The bulk molybdenum disulfide and n-butyllithium are stirred under an inert atmosphere. The resulting product is washed and filtered with an organic solvent to obtain lithium-intercalated molybdenum disulfide.

[0015] S12. Lithium-intercalated molybdenum disulfide is added to deionized water and subjected to ultrasonic oscillation for exfoliation. Unexfoliated material is removed by centrifugation to obtain an aqueous solution of single-layer molybdenum disulfide nanosheets with negative surface charge.

[0016] Preferably, in step S11, the mass-to-volume ratio of molybdenum disulfide to n-butyllithium is 1 g: 5-20 mL.

[0017] Preferably, in step S11, the stirring time is 48 to 120 hours.

[0018] Preferably, in step S11, the inert atmosphere includes argon, nitrogen, etc.

[0019] Preferably, in step S11, the organic solvent is n-hexane, pentane, n-heptane, or methanol, etc.

[0020] Preferably, in step S12, the mass-to-volume ratio of the lithium-intercalated molybdenum disulfide to deionized water is 1g:0.5-3L.

[0021] Preferably, in step S12, the ultrasonic oscillation power is 300W and the time is 1 to 3 hours.

[0022] Preferably, in step S12, the centrifugation speed is 3000 r / min and the time is 5 to 30 min.

[0023] Preferably, in step S2, the step of self-assembling a molybdenum disulfide / organic small molecule hybrid by electrostatic adsorption of negatively charged monolayer molybdenum disulfide nanosheets and positively charged organic small molecule groups is as follows:

[0024] A solution containing positively charged small organic molecule groups was added to an aqueous solution of negatively charged molybdenum disulfide nanosheets. The mixture was stirred to induce molybdenum disulfide flocculation. After the reaction was completed, the mixture was allowed to stand, and the supernatant was removed by centrifugation to obtain a molybdenum disulfide / small organic molecule hybrid.

[0025] Preferably, the solution containing positively charged small organic molecule groups includes one or both of tetramethylammonium hydroxide solution (solvent is water) and tetrabutylammonium hydroxide solution (solvent is water). Tetrabutylammonium hydroxide solution is preferred. The positively charged small organic molecule group in the tetramethylammonium hydroxide solution is (CH3)4N. + The positively charged small organic molecule group in tetrabutylammonium hydroxide solution is (CH3(CH2)3)4N. + .

[0026] Preferably, the concentration of the solution containing positively charged small organic molecule groups is 0.1–5 M.

[0027] Preferably, the volume ratio of the aqueous solution of the negatively charged molybdenum disulfide nanosheets to the solution containing positively charged organic small molecule groups is 20–200:1. This ratio can induce rapid flocculation of molybdenum disulfide.

[0028] Preferably, the stirring time is 10 to 60 minutes.

[0029] Preferably, after the reaction is complete, stirring is continued to ensure homogeneity, followed by standing. The flocculated product settles at the bottom of the container. Finally, the supernatant is removed by light centrifugation to obtain molybdenum disulfide / organic small molecule hybrid.

[0030] Preferably, in step S3, the drying is vacuum freeze drying, with a drying temperature below -50°C, a vacuum degree of 1 to 20 Pa, and a drying time of 12 to 120 hours.

[0031] Preferably, in step S3, the annealing temperature is 250–400°C and the annealing time is 1–4 hours.

[0032] More preferably, the annealing temperature is 300°C and the annealing time is 1 hour. Under this annealing temperature condition, the small organic molecule groups can be fully carbonized.

[0033] The present invention also provides a molybdenum disulfide / carbon superlattice material prepared by the above preparation method, which has high conductivity, stable structure and fast ion diffusion kinetics.

[0034] This invention also provides the application of the aforementioned molybdenum disulfide / carbon superlattice material in the cathode of a sulfide-based all-solid-state lithium metal battery. The molybdenum disulfide / carbon superlattice material of this invention exhibits high conductivity; when used as the cathode in an all-solid-state lithium battery, no additional conductive agent is required, and the battery demonstrates high electrochemical performance and stability. When used as a composite cathode, the molybdenum disulfide / carbon superlattice material of this invention achieves a reversible capacity of up to 591.6 mAh g⁻¹ after 100 cycles, with a retention rate as high as 87.1%.

[0035] Compared with the prior art, the present invention has at least the following beneficial effects:

[0036] (1) The method of the present invention has the advantages of simple process flow, easy operation and good controllability, and is suitable for large-scale industrial production.

[0037] (2) The alternating stacking structure of molybdenum disulfide and carbon layers in the molybdenum disulfide / carbon superlattice material prepared by the present invention can adapt to the volume change during the charge-discharge cycle and promote the rapid diffusion of lithium ions. The carbon layer is confined and stabilized between the layers of molybdenum disulfide nanosheets, which can effectively improve the degradation problem of sulfide electrolytes. It has high conductivity, stable structure and fast ion diffusion kinetics.

[0038] (3) The molybdenum disulfide / carbon superlattice material of the present invention has high conductivity, so when used as the positive electrode of all-solid-state lithium battery, no additional conductive agent needs to be added, and the electrochemical performance and stability of the battery can be greatly improved. Attached Figure Description

[0039] Figure 1 The image shows the XRD pattern of the molybdenum disulfide / carbon superlattice material in Example 1.

[0040] Figure 2The image shows the SEM spectrum of the molybdenum disulfide / carbon superlattice material from Example 1.

[0041] Figure 3 The all-solid-state lithium metal battery of Example 1, using a 1:1 mixture of molybdenum disulfide / carbon superlattice material and sulfide electrolyte as the positive electrode, operates at 0.1C at 0.5–3.0V (vs Li / Li + The cyclic performance diagram within )

[0042] Figure 4 The all-solid-state lithium metal battery of Example 2, which uses a 1:1 mixture of molybdenum disulfide / carbon superlattice material and sulfide electrolyte as the positive electrode, operates at 0.1C and 0.5–3.0V (vs Li / Li + The cyclic performance diagram within )

[0043] Figure 5 The all-solid-state lithium metal battery of Example 3, which uses a 1:1 mixture of molybdenum disulfide / carbon superlattice material and sulfide electrolyte as the positive electrode, operates at 0.1C and 0.5–3.0V (vs Li / Li + The cyclic performance diagram within )

[0044] Figure 6 The image shows the XRD pattern of the bulk molybdenum disulfide material in Comparative Example 1.

[0045] Figure 7 The image shows the SEM spectrum of the bulk molybdenum disulfide material in Comparative Example 1.

[0046] Figure 8 The all-solid-state lithium metal battery of Comparative Example 1, using a 1:1 mixture of bulk lithium metal and sulfide electrolyte as the positive electrode, operates at 0.1C, 0.5–3.0 V (vs Li / Li). + The cyclic performance diagram within ) Detailed Implementation

[0047] The following detailed description, in conjunction with specific embodiments, provides a more comprehensive understanding of the molybdenum disulfide / carbon superlattice material of the present invention, its preparation method, and its applications. It should be understood that the following embodiments are merely illustrative and explanatory of the invention and should not be construed as limiting the scope of protection of the invention. All technologies implemented based on the above-described content of the present invention are covered within the scope of protection intended by the present invention.

[0048] Unless otherwise stated, the raw materials and reagents used in the following examples are commercially available products or can be prepared by known methods.

[0049] Example 1

[0050] (1) Weigh 1g of blocky molybdenum disulfide and add 10mL of n-butyllithium. Stir in an argon-filled glove box for 72h. Then wash and filter three times with 10mL of n-hexane to collect the lithium-intercalated molybdenum disulfide. Add the collected lithium-intercalated molybdenum disulfide to 1L of deionized water and sonicate at 300W for 2h to promote exfoliation. Centrifuge at 3000r / min for 10min to remove unexfoliated material to obtain an aqueous solution of negatively charged monolayer molybdenum disulfide nanosheets.

[0051] (2) Take 10 mL of 2M containing positively charged small organic molecules (CH3(CH2)3)4N + A tetrabutylammonium hydroxide solution was added to 500 mL of an aqueous solution of negatively charged molybdenum disulfide nanosheets, and the mixture was stirred for 10 min to induce molybdenum disulfide flocculation. After the reaction was complete, stirring was continued for 30 min to ensure homogeneity. The mixture was then allowed to stand for 1 h, during which the flocculated product precipitated at the bottom of the beaker. Finally, the supernatant was removed by gentle centrifugation to obtain the molybdenum disulfide / tetrabutylammonium hydroxide hybrid.

[0052] (3) The molybdenum disulfide / tetrabutylammonium hydroxide hybrid was freeze-dried in vacuum at a vacuum of 1 Pa for 72 h, and then annealed at 300 °C for 1 h to obtain molybdenum disulfide / carbon superlattice material.

[0053] (4) The obtained molybdenum disulfide / carbon composite material was characterized. Figure 1 The XRD pattern of the molybdenum disulfide / carbon superlattice material prepared according to the scheme in Example 1 is shown below. Figure 1 The main characteristic diffraction peaks of the molybdenum disulfide / carbon superlattice (002) crystal plane are at ~8.3°, and the second-order diffraction peaks of the (004) crystal plane of the superlattice are at ~15.9°. Figure 2 The corresponding SEM images show that the molybdenum disulfide / carbon superlattice exhibits a flexible two-dimensional morphology. The loose structure can adapt to volume changes during charge-discharge cycles, improves contact with the sulfide solid electrolyte, and facilitates the rapid diffusion of lithium ions.

[0054] (5) The obtained molybdenum disulfide / carbon superlattice material was mixed with a sulfide solid electrolyte at a 1:1 ratio to prepare a composite cathode material, which was then assembled into an all-solid-state lithium metal battery for electrochemical testing. For example... Figure 3 As shown, this data graph illustrates the voltage characteristics of the fabricated all-solid-state lithium battery at 0.1C, ranging from 0.5 to 3.0 V (vs Li / Li). + The charge-discharge cycle diagram after 100 cycles shows that the composite cathode maintains excellent cycle stability. After 100 cycles, the reversible capacity is 591.6 mAh g-1, with a retention rate of 87.1%.

[0055] Example 2

[0056] (1) Weigh 1g of blocky molybdenum disulfide and add 10mL of n-butyllithium. Stir in an argon-filled glove box for 72h. Then wash and filter three times with 10mL of n-hexane to collect the lithium-intercalated molybdenum disulfide. Add the collected lithium-intercalated molybdenum disulfide to 1L of deionized water and sonicate at 300W for 2h to promote exfoliation. Centrifuge at 3000r / min for 10min to remove unexfoliated material to obtain an aqueous solution of negatively charged monolayer molybdenum disulfide nanosheets.

[0057] (2) Take 10 mL of 5M containing a positively charged small organic molecule group (CH3(CH2)3)4N + A tetrabutylammonium hydroxide solution was added to 500 mL of an aqueous solution of negatively charged molybdenum disulfide nanosheets, and the mixture was stirred for 10 min to induce molybdenum disulfide flocculation. After the reaction was complete, stirring was continued for 30 min to ensure homogeneity. The mixture was then allowed to stand for 1 h, during which the flocculated product precipitated at the bottom of the beaker. Finally, the supernatant was removed by gentle centrifugation to obtain the molybdenum disulfide / tetrabutylammonium hydroxide hybrid.

[0058] (3) The molybdenum disulfide / tetrabutylammonium hydroxide hybrid was freeze-dried in vacuum at a vacuum of 1 Pa for 72 h, and then annealed at 300 °C for 1 h to obtain molybdenum disulfide / carbon superlattice material.

[0059] (4) The obtained molybdenum disulfide / carbon superlattice material was mixed with a sulfide solid electrolyte at a 1:1 ratio to prepare a composite cathode material, which was then assembled into an all-solid-state lithium metal battery for electrochemical testing. For example... Figure 4 As shown, this data graph illustrates the voltage characteristics of the fabricated all-solid-state lithium battery at 0.1C, ranging from 0.5 to 3.0 V (vs Li / Li). + The image shows the charge-discharge cycle diagram after 100 cycles. It can be seen that the composite cathode maintains excellent cycle stability, with a reversible capacity of 540.8 mAh g⁻¹ after 100 cycles, representing a retention rate of 86.8%.

[0060] Example 3

[0061] (1) Weigh 1g of blocky molybdenum disulfide and add 10mL of n-butyllithium. Stir in an argon-filled glove box for 72h. Then wash and filter three times with 10mL of n-hexane to collect the lithium-intercalated molybdenum disulfide. Add the collected lithium-intercalated molybdenum disulfide to 1L of deionized water and sonicate at 300W for 2h to promote exfoliation. Centrifuge at 3000r / min for 10min to remove unexfoliated material to obtain an aqueous solution of negatively charged monolayer molybdenum disulfide nanosheets.

[0062] (2) Take 10 mL of 0.5 M organic small molecule group (CH3(CH2)3)4N containing positively charged groups. +A tetrabutylammonium hydroxide solution was added to 500 mL of an aqueous solution of negatively charged molybdenum disulfide nanosheets, and the mixture was stirred for 10 min to induce molybdenum disulfide flocculation. After the reaction was complete, stirring was continued for 30 min to ensure homogeneity. The mixture was then allowed to stand for 1 h, during which the flocculated product precipitated at the bottom of the beaker. Finally, the supernatant was removed by gentle centrifugation to obtain the molybdenum disulfide / tetrabutylammonium hydroxide hybrid.

[0063] (3) The molybdenum disulfide / tetrabutylammonium hydroxide hybrid was freeze-dried in vacuum at a vacuum of 1 Pa for 72 h, and then annealed at 300 °C for 1 h to obtain molybdenum disulfide / carbon superlattice material.

[0064] (4) The obtained molybdenum disulfide / carbon superlattice material was mixed with a sulfide solid electrolyte at a 1:1 ratio to prepare a composite cathode material, which was then assembled into an all-solid-state lithium metal battery for electrochemical testing. For example... Figure 5 As shown, this data graph illustrates the voltage characteristics of the fabricated all-solid-state lithium battery at 0.1C, ranging from 0.5 to 3.0 V (vs Li / Li). + The image shows the charge-discharge cycle diagram after 100 cycles. It can be seen that the composite cathode maintains excellent cycle stability, with a reversible capacity of 482.9 mAh g⁻¹ after 100 cycles, representing a retention rate of 86.2%.

[0065] Comparative Example 1

[0066] (1) The bulk molybdenum disulfide was characterized. Figure 6 The XRD pattern of the bulk molybdenum disulfide in Comparative Example 1 is shown below. Figure 6 The main characteristic diffraction peaks of the bulk molybdenum disulfide (002) crystal plane are at ~14.4°. Figure 7 The corresponding SEM images show that molybdenum disulfide exhibits a dense plate-like structure.

[0067] (2) A composite cathode material was prepared by mixing bulk molybdenum disulfide with a sulfide solid electrolyte at a 1:1 ratio to assemble an all-solid-state lithium metal battery for electrochemical testing. For example... Figure 8 As shown, this data graph illustrates the voltage characteristics of the fabricated all-solid-state lithium battery at 0.1C, ranging from 0.5 to 3.0 V (vs Li / Li). + The image shows the charge-discharge cycle diagram after 100 cycles. It can be seen that the composite cathode maintains a low reversible capacity; after 100 cycles, the reversible capacity is only 110.5 mAh g⁻¹, with a retention rate of 38.4%.

[0068] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing a molybdenum disulfide / carbon superlattice material for the cathode of a sulfide-based all-solid-state lithium metal battery, characterized in that, Includes the following steps: S1. Bulk molybdenum disulfide is exfoliated into single-layer molybdenum disulfide nanosheets with negative surface charge by chemical intercalation exfoliation method; S2. Molybdenum disulfide nanosheets with negative surface charge are electrostatically adsorbed and self-assembled with positively charged organic small molecule groups to form a molybdenum disulfide / organic small molecule hybrid. The specific steps are as follows: a solution containing positively charged organic small molecule groups is added to an aqueous solution of molybdenum disulfide nanosheets with negatively charged surfaces, and the mixture is stirred to induce molybdenum disulfide flocculation. After the reaction is completed, the mixture is allowed to stand, and the supernatant is removed by centrifugation to obtain molybdenum disulfide / organic small molecule hybrid. The solution containing positively charged small organic molecule groups includes one or both of tetramethylammonium hydroxide solution and tetrabutylammonium hydroxide solution; S3. Molybdenum disulfide / organic small molecule hybrid is subjected to vacuum freeze-drying and annealing to obtain molybdenum disulfide / carbon superlattice material.

2. The preparation method according to claim 1, characterized in that, In step S1, the step of exfoliating bulk molybdenum disulfide into negatively charged monolayer molybdenum disulfide nanosheets using a chemical intercalation exfoliation method is as follows: S11. The bulk molybdenum disulfide and n-butyllithium are stirred under an inert atmosphere. The resulting product is washed and filtered with an organic solvent to obtain lithium-intercalated molybdenum disulfide. S12. Lithium-intercalated molybdenum disulfide is added to deionized water and subjected to ultrasonic oscillation for exfoliation. Unexfoliated material is removed by centrifugation to obtain an aqueous solution of single-layer molybdenum disulfide nanosheets with negative surface charge.

3. The preparation method according to claim 2, characterized in that, In step S11, the mass-to-volume ratio of molybdenum disulfide to n-butyllithium is 1 g: 5~20 mL; the stirring time is 48~120 h.

4. The preparation method according to claim 3, characterized in that, In step S12, the mass-to-volume ratio of the lithium-intercalated molybdenum disulfide to deionized water is 1g:0.5~3L, the ultrasonic oscillation power is 300 W, and the time is 1~3 h.

5. The preparation method according to claim 1, characterized in that, The concentration of the solution containing positively charged small organic molecule groups is 0.1~5 M; the volume ratio of the aqueous solution of the negatively charged molybdenum disulfide nanosheets to the solution containing positively charged small organic molecule groups is 20~200:

1.

6. The preparation method according to claim 1, characterized in that, The stirring time is 10~60 min.

7. The preparation method according to claim 1, characterized in that, In step S3, the annealing temperature is 250~400℃ and the annealing time is 1~4h.

8. The molybdenum disulfide / carbon superlattice material prepared by the preparation method according to any one of claims 1-7.

Citation Information

Patent Citations

  • Binary transition metal sulfide material and application thereof

    CN113943016A

  • Preparation and application method of graphene intercalated molybdenum disulfide composite material

    CN112875754A